Alcoolismo crônico como um possível fator de risco para a Leishmaniose Cutânea Disseminada - Sindeaux Filho, Pedro Delcy Torres (2017)
Disseminated cutaneous leishmaniasis (DCL) is an agressive clinical form of tegumentar leshmaniasis and is characterised by multiple ulcers and papules (>10) present in more than two noncontiguos body part. There have been a significant increasing in DCL cases in the brazilian northeast region over the past two decades which indicate the need for research in this increment related factors. Objectives: To evaluate if there is a relationship between chronic alcoholism and occurrence of disseminated leishmaniasis. Specifically characterize clinical and epidemiological data, histopathological findings, amount and frequency of alcohol intake in patients with DL. Patients with localized cutaneous form of leismaniasis (LCL) were used as control group. Material and methods: Case-control study conducted with 12 patients with DCL and 36 patients with LCL paired by sex and age. Histopathological, morphometric and immunohistochemical for leishmania analysis was performed in biopsies from ulcerated lesions. A specific questionnaire was used to collect demographic data ando to investigate alcohol consumption. Results and Discussion: Of the 120 patients with cutaneous leismaniasis dignosed in Baturité, Ceará, from the period from 2013 to 2016, 10% of them presented with DCL. The prevalence of DCL was higher among men, agricultural workers, living in countryside. The number of lesions of the patients ranged from 11 to 184, distributed in more than one body segment with main involvement of the extremities. The mean time of disease evolution from the initial symptoms to dissemination stage was 14 weeks. Was observed in the dermis, a moderate to severe chronic inflammatory lymphohistioplasmocytic infiltrate, displaying immature granulomas. Amastigotes were identified in 87.5% of DCL patients. A positive correlation was observed between the parasite load and the intensity of the inflammatory infiltrate (R2 = 0.682 and p = 0.0115) as well as the plasmacyte frequency (R2 = 0.99 and p <0.0001). It was found that patients with DCL presented an abusive consumption of alcohol (> 60g / day) (OR = 15, 95% CI = 2.8 - 82, p <0.001) and dependence (AUDIT ≥ 20) 95% CI = 3.6-345, p <0.001). Conclusion: The abuse of alcohol intake was directly associated with the occurrence of DCL.